PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA DENGAN MENERAPKAN METODE DISKUSI KELOMPOK PLENO PADA MATA KULIAH EVOLUSI DI STKIP PGRI SUMBAR - Ruth Rize Paas Megahati; Meliya Wati; Elza Safitri (Postgraduate, University of Mataram, 2015)
Lack of understanding of concepts and facts in the Evolution subject leads to low activity and student learning achievement. That are caused students simply expect information from lectures who are still using regular discussion. The purpose of this research is to improve the activity and student learning achievement at the Evolution course. Learning activities that are studied, among others asking, answering questions, the moderator, presenter on discussions, and taking note of the lecturer. This type of research is a class action research in the class that may have activity and low learning achievement. Learning achievement assessed is cognitive aspect only the cognitive. Increasing of activity and student learning achievement will be done by using the method of group learning plenary discussion. It a method in which all participants can be used to describe a particular topic or concept so the understanding of the participants are expected to be the same. Application of the method plenary discussion on the course of evolution can improve the activity and student learning achievement of Biology education students of STKIP PGRI of West Sumatra